A foot tumour as late cutaneous Lyme borreliosis: a new entity or a variant of an inflammatory proliferative reaction to Borrelia burgdorferi?. (20th October 2017) - Hofmann, H.
Abstract : Linked Article:Bauvin et al. Br J Dermatol 2017; 177:1127–1130 .